The role of p53 in hypoxia-induced apoptosis - Poole, R (2010)
Tumour hypoxia is associated with resistance to therapy, increased aggressiveness and a poor patient prognosis. The tumour suppressor p53 causes apoptosis in response to hypoxia and therefore hypoxic tumours select for the loss of p53. In this work was we have investigated the post-translational modifications and binding partners of p53 in hypoxia. Furthermore, we investigated the p53-dependent gene expression changes in hypoxia. We have shown that p53 is stabilised and phosphorylated in hypoxia, and that there are some differences between p53 modifications in hypoxia and those in response to DNA damage. We have also shown that N-terminal phosphorylations of p53 at serines 20 and 46 are important, but not essential for induction of apoptosis in hypoxia. Strikingly we observed that DNA binding of p53 is essential for hypoxia-induced apoptosis. We have seen, for the first time, that p53 induces a subset of its targets in hypoxia and that these proteins do have previously reported roles in apoptosis. In addition, it is possible that p53 can induce miRNA expression in hypoxia. Moreover, preliminary work suggests that p53 is part of a complex in hypoxia. Elucidating the proteins that make up this complex could prove important for understanding the mechanism of p53-induced apoptosis in hypoxia.